Beispiel Nr: 16
$ \text{Gegeben:} ax^{2}+bx+c=0 \\ \text{Gesucht:} \\ \text{Lösung der Gleichung} \\ \\ ax^{2}+bx+c=0 \\ \textbf{Gegeben:} \\ x^2-8x-20 =0 \\ \\ \textbf{Rechnung:} \\ \begin{array}{l|l|l} \begin{array}{l} \text{a-b-c Formel}\\ \hline \\ 1x^{2}-8x-20 =0 \\ x_{1/2}=\displaystyle\frac{+8 \pm\sqrt{\left(-8\right)^{2}-4\cdot 1 \cdot \left(-20\right)}}{2\cdot1} \\ x_{1/2}=\displaystyle \frac{+8 \pm\sqrt{144}}{2} \\ x_{1/2}=\displaystyle \frac{8 \pm12}{2} \\ x_{1}=\displaystyle \frac{8 +12}{2} \qquad x_{2}=\displaystyle \frac{8 -12}{2} \\ x_{1}=10 \qquad x_{2}=-2 \end{array}& \begin{array}{l} \text{p-q Formel}\\ \hline \\ \\ x^{2}-8x-20 =0 \\ x_{1/2}=\displaystyle -\frac{-8}{2}\pm\sqrt{\left(\frac{\left(-8\right)}{2}\right)^2- \left(-20\right)} \\ x_{1/2}=\displaystyle 4\pm\sqrt{36} \\ x_{1/2}=\displaystyle 4\pm6 \\ x_{1}=10 \qquad x_{2}=-2 \end{array}\\ \end{array}$